FIGURATIVE LANGUAGE IN ED SHEERAN’S SONG LYRICS - Siska Sinaga; Saut Maruli Siburian; Gongsar Silaban (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2021)
This article deals with "Figurative Language in Ed Sheeran’s Song Lyrics". The objectives of the study were to find out the types of figurative language in Ed Sheeran’s song lyrics and to find out the meaning of figurative language in Ed Sheeran’s song lyrics. The method of the study applied to the research is a qualitative method. The results of this study were 42 figurative sentences found from 9 Ed Sheeran Song Lyrics which consist of metaphor with 14 data, hyperbole with 16 data, personification with 3 data, and simile with 9 data.